IMPLEMENTASI EXPERENTIAL LEARNING & PLACEMENT CENTER UNTUK MENINGKATKAN KETERSERAPAN LULUSAN AKUNTANSI - Rudy Suryanto (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2016)
Educational unemployment is a big issue in Indonesia. Unemployment in 2014 is 5.94% and surprisingly among them around 41.8% is educated. The distribution of educated unemployment are higher education graduates 12.78%, high school graduates 11.9%, vocational high school graduates 11.87%, junior high school graduates 7.45%, and elementary school graduates 3.81%. This fact was well known and considered by education institution and government. There were a lot of initiatives already taken such as link-and-match concept during Soeharto era, competency based curriculum and recently is national qualification framework standard (SKKNI). Those initiatives aimed to narrow down the gap between industry and education sector. However the result of those initiatives is still limited. This paper argue that we should follow the India example on how to train the nearly graduate to prepare entering working environment. Based on the evidence in the field, the difficulty of graduates to enter the working environment is not only because lack of technical skills, but more because of lack of soft skills. This paper suggests a model of using experiential learning and placement center to enhance the ability of graduate to adapt into working environment.Â Keywords : Accounting Education, Experential Learning, Placement Center, Graduate Employability, Educational Unemployment